Risk factors of emergence and reason of low efficiency of treatment endodontoparodontalnykh of lesions (Эндодонтия Today)
On the basis of clinical trial major factors of emergence and the reason of noneffective treatment the endodontoparodontalnykh of lesions (EPP) are established. Major factors of risk of emergence of EPP at adults are the single or multiple parodontalny pockets more than 5 mm in depth caused by the chronic periodontal disease proceeding against the background of chronic periapical processes of the teeth which are followed by the expressed inflammatory resorption of a bone tissue which centers according to X-ray inspection belong to the granulating periodontitis and exceed in the diameter of 7 mm. The reasons reducing efficiency of complex treatment of EPP are: the unsatisfactory result of endodontichesky treatment, the apical granulating periodontitis, augmentation of borders of a bone tissue with low x-ray density in the field of an apical periodontium after endodontichesky treatment at radiological inspection, existence of a vertical inflammatory resorption of interdental and (or) interroot septums, a relative indicator of a reduction later after treatment less than 46%, the initial parodontalny Rassel index is higher 3 months than 6 points.